Learning fast accurate movements requires intact frontostriatal circuits - Shabbott, Britne; Ravindran, Roshni; Schumacher, Joseph W.; Wasserman, Paula B.; Marder, Karen S.; Mazzoni, Pietro (Frontiers in Human Neuroscience, 2013)
The basal ganglia are known to play a crucial role in movement execution, but their importance for motor skill learning remains unclear. Obstacles to our understanding include the lack of a universally accepted definition of motor skill learning (definition confound), and difficulties in distinguishing learning deficits from execution impairments (performance confound). We studied how healthy subjects and subjects with a basal ganglia disorder learn fast accurate reaching movements, and we addressed the definition and performance confounds by: 1) focusing on an operationally defined core element of motor skill learning (speed-accuracy learning), and 2) using normal variation in initial performance to separate movement execution impairment from motor learning abnormalities. We measured motor skill learning learning as performance improvement in a reaching task with a speed-accuracy trade-off. We compared the performance of subjects with Huntington’s disease (HD), a neurodegenerative basal ganglia disorder, to that of premanifest carriers of the HD mutation and of control subjects. The initial movements of HD subjects were less skilled (slower and/or less accurate) than those of control subjects. To factor out these differences in initial execution, we modeled the relationship between learning and baseline performance in control subjects. Subjects with HD exhibited a clear learning impairment that was not explained by differences in initial performance. These results support a role for the basal ganglia in both movement execution and motor skill learning.